The study of pubertal stage and age of menarche in girls in Isfahan province, Iran - Nafiseh Mozafarian; Mahin Hashemipour; Mohammad Reza Maracy; Masoumeh Pourrajab; Razieh Omidi; Roya Kelishadi (BMC Pediatrics)
Abstract Background The onset age of pubertal changes varies widely among girls and has undergone changes over time around the world. This study aimed to determine the age of onset of puberty in healthy Iranian girls living in Isfahan province. Methods This cross- sectional study was conducted among 13,886 students aged 6–18 years. They were selected by multistage random cluster sampling from urban and rural areas of Isfahan province of Iran. Pubertal stage was determined according the 5-level Tanner stages proposed by Marshall and Tanner. Trained physicians determined the breast development through both visual inspection and palpation, in addition, mothers assessed their daughter’s pubic hair growth using Tanner’s Sexual Maturation Scale (SMS) by comparison to standard pictures. The data were analyzed by the status quo method. Probit regression analysis was used to evaluate the median age of onset for each characteristic including menarche, breast and pubic hair. Results A total of 13,886 healthy girls with mean age (SD) of 11.97 (2.9) were studied. Overall 6968 (50.2%) girls experienced menstruation with a median (95%CI) age of 12.05(11.88–12.21) years at its onset. The median age for onset of breast development was 9.89 (95% CI: 9.77 − 10.02) years and for onset of pubic hair development was 10.14 (95% CI: 9.88– 10.39) years. The 3rd percentile for breast stage 2 (B2) and pubic hair stage 2 (PH2) was 6.85 and 6.75 years, respectively, and the 97th percentile for B2 and PH2 was 12.94and 13.54 years, respectively. Conclusion According to our findings, the onset of puberty before 6.85 years should be considered as precocious puberty for Iranian girls. Our study indicated the secular trend toward earlier menarche in girls. Nationally representative surveys and longitudinal studies are necessary to determine the exact age of puberty for future international comparisons.